Motivación aparente en actos administrativos de desvinculación de servidores públicos bajo la Ley Orgánica de Integridad Pública del Ecuador - Klever Mauricio Márquez Vega; Bárbara Nicole Aguirre Tene (Emergentes - Revista Científica, 2026)
This article analyzes the constitutional guarantee of reason-giving in administrative acts in Ecuador, based on the applicable constitutional and statutory framework, the jurisprudential criteria established in Judgment No. 1158-17-EP/21 of Ecuador’s Constitutional Court, and their application to dismissal acts issued during the effective period of the Organic Law on Public Integrity (LOIP). Using a documentary approach with explanatory scope, the study applied legal-dogmatic, analytical-synthetic, and deductive methods. Two protection-action judgments were purposively selected because they reproduce the challenged administrative acts and allow them to be assessed against the constitutional standard of motivation. The results show, in the two cases analyzed, forms of apparent motivation: an ordinary contract termination that failed to address reinforced constitutional safeguards, and a position-suppression decision based on general rules without individualized factual reasoning or sufficient verification of special-protection circumstances. The normative analysis also showed that the dismissal route based on insufficient performance under the amended Article 80 of the Organic Law of the Public Service (LOSEP) required an administrative disciplinary proceeding. The study concludes that merely citing legal rules does not satisfy the duty to provide reasons when those rules are not connected to the public servant’s specific circumstances. Five legal guidelines are proposed to strengthen the validity of dismissal acts and respect for due process.